Numerical Simulation of the Effect of Different Number Leading Edge Winglets on the Fan-Wing Aerodynamic Characteristics - Du Siliang; Zhao Qijun; Tang Zhengfei (International Journal of Aerospace Engineering)
The generation of lift and thrust mainly depends on the formation of low-pressure vortices above the arc groove on the leading edge of the Fan-wing, which makes the lift and thrust have a strong coupling relationship. How to decouple and control the lift and thrust is the key to further engineering application of the Fan-wing. Normally, the geometric parameters of the Fan-wing airfoil were determined; the leading edge opening angle has the greatest influence on the aerodynamic performance. Therefore, the method of installing leading edge winglets on the leading edge of a base Fan-wing airfoil was considered to change the opening angle of the leading edge of the Fan-wing. Through numerical simulation, the effects of single, double, and triple leading edge winglets on lift and thrust of the Fan-wing at different installation angles, inflow velocities, and angles of attack were compared and analyzed. The results show that by controlling the angle of the leading edge winglet, not only the lift and thrust of the fan can be improved but also the strength and position of the low-pressure vortices can be controlled, so as to meet the active control requirements of the aerodynamic moment of the Fan-wing, and then the attitude of the Fan-wing aircraft can be controlled.